A STUDY OF THE FARMERS MOVEMENT IN INDIA: A STUDY OF THEIR POLITICAL ACTIVISM AND IMPACT - Prasad Paswan, Mr. Ravi Bhushan (International Journal of Multidisciplinary Research and Studies, 2020)
He argues that one of the most important contributing factors to peasant uprising throughout history has been the indebtedness of the peasants as a result of their low income in relation to their necessities. Their small holdings, low productivity, low pricing for their produce relative to the high cost of their inputs, high taxes, excessive capitalization and mechanization, phony inputs, inadequate irrigation infrastructure, and other problems could all contribute to their low incomes. He explains the difficulties faced by small holdings before arriving at the conclusion that peasant proprietors cannot escape going into debt unless they are exceptionally diligent and frugal or unless they have an additional source of income (ibid:280). He remarked about the Indian province of Bihar, "Bihar is agriculturally the most prosperous province in India, and is likely also the most indebted” In order to create dependable irrigation systems and develop previously uncultivated territory, colonial authorities in Bihar's Indus basin constructed a number of canal colonies in the second part of the nineteenth century.